Change agency and reproductive agency in the course of industrial path evolution. Issue 4 (3rd April 2021) - Bækkelund, Nora G.
ABSTRACT: The literature integrating an agency perspective with evolutionary economic geography (EEG) has tended to focus on change agency. This paper introduces a distinction between change agency and reproductive agency. The variegated agency understanding is integrated within a path-as-process perspective. By investigating three cases of rural tourism development, changes in types of agency in the course of path evolution are elucidated. It emerges that both change and reproductive agency are important for industry path development. Thus, the article contributes to a more dynamic and nuanced understanding of the role of agency in path evolution, expanding the hitherto change-oriented agency literature in EEG.